Berengeria rafaeli, gen. nov., sp. nov. de Reduviinae da Reserva Ducke, Estado do Amazonas, Brasil (Hemiptera-Heteroptera, Reduviidae) - Gil-santana, Hélcio R.; Silva, Alexandre Coletto da (Acta Amazonica, 2005)
A new genus and species of Reduviinae (Hemiptera-Heteroptera, Reduviidae) from the Amazonas State, Brazil are described. A taxonomic key for American genera of Reduviinae is given.
Berengeria rafaeli, n. gen., n. sp. of Reduviinae from Reserva Ducke, Amazonas State, Brazil (Hemiptera-Heteroptera, Reduviidae)
Keywords: Reduviinae; Neotropical; Amazon; Reduviinae; Neotropical; Amazônia